2019
DOI: 10.18551/rjoas.2019-07.36
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership Style and Work Life Balance: The Effect on Employee Satisfaction Through Employee Engagement

Abstract: Leaders of any organization are expected to carry out tasks with limited resource to the maximum level in order to maintain the competitive edge and sustain profitability position of the organization. In other side, employees are looking for ways that will help them balance between work and personal life effectively. Successful organizations know that employee satisfaction, performance and employee engagement are crucial. The objective of this research is to analyze the impact of work life balance and transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…In the test results, it was found that employee engagement influences job satisfaction. These results are in line with research conducted by Diyanto et al (2019); Suryanto et al (2019); Madan and Srivastava (2015); Vorina et al (2017);Thakur (2014) and Biswas and Bhatnagar (2013). This shows that when a company has a high level of employee engagement in its employees, then this has an impact on the job satisfaction of employees.…”
Section: Result Discussion and Conclusion Discussionsupporting
confidence: 90%
“…In the test results, it was found that employee engagement influences job satisfaction. These results are in line with research conducted by Diyanto et al (2019); Suryanto et al (2019); Madan and Srivastava (2015); Vorina et al (2017);Thakur (2014) and Biswas and Bhatnagar (2013). This shows that when a company has a high level of employee engagement in its employees, then this has an impact on the job satisfaction of employees.…”
Section: Result Discussion and Conclusion Discussionsupporting
confidence: 90%
“…IT employees who own WLB carry out their work wholeheartedly, more productive, and show a positive emotional attitude in their environment. This finding is in line with some opinions and studies that have been done before (Greenhaus and Powell, 2006;Crede et al, 2007;Soomro et al, 2018;Talukder et al, 2018;Kaushal, 2019;Suryanto et al, 2019;Abdirahman et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Individuals who experience WLB will be more satisfied with their work because they participate in activities with roles that are prominent to them (Greenhaus and Powell, 2006). Previous research has confirmed that WLB has a positive effect on job satisfaction (Crede et al, 2007;Talukder et al, 2018;Suryanto et al, 2019). Based on the above statements, we propose the following hypothesis:…”
Section: B Work-life Balance and Job Satisfactionmentioning
confidence: 89%
“…Empirical results show that a good work-life balance can increase the job satisfaction of telecommunications workers supporting partner companies in Indonesia (Erwin et al, 2019). It is also hypothesized that work-life balance can increase job satisfaction among interviewed workers who are continuing their education in Banten Province (Sukmayuda & Kustiawan, 2022).…”
Section: Relationship Of Work-life Balance and Job Satisfactionmentioning
confidence: 99%